Globally altered epigenetic landscape and delayed osteogenic differentiation in H3.3-G34W-mutant giant cell tumor of bone - Lutsik, Pavlo; Baude, Annika; Mancarella, Daniela; Öz, Aliye Simin; Kühn, Alexander; Toth, Reka; Hey, Joschka; Toprak, Umut; Lim, Jinyeong; Viet Hanh Nguyen; Jiang, Chao; Mayakonda Thippeswamy, Anand; et al. (Nature Communications, 2020)
The neoplastic stromal cells of giant cell tumor of bone (GCTB) carry a mutation in H3F3A, leading to a mutant histone variant, H3.3-G34W, as a sole recurrent genetic alteration. We show that in patient-derived stromal cells H3.3-G34W is incorporated into the chromatin and associates with massive epigenetic alterations on the DNA methylation, chromatin accessibility and histone modification level, that can be partially recapitulated in an orthogonal cell line system by the introduction of H3.3-G34W. These epigenetic alterations affect mainly heterochromatic and bivalent regions and provide possible explanations for the genomic instability, as well as the osteolytic phenotype of GCTB. The mutation occurs in differentiating mesenchymal stem cells and associates with an impaired osteogenic differentiation. We propose that the observed epigenetic alterations reflect distinct differentiation stages of H3.3 WT and H3.3 MUT stromal cells and add to H3.3-G34W-associated changes.
Gesehen am 21.01.2021